Front Cover: A Comprehensive Analysis of Symmetric Arginine Dimethylation in Colorectal Cancer Tissues Using Immunoaffinity Enrichment and Mass Spectrometry. Issue 15 (18th August 2020) - Lim, Yongchul; Park, Yae Eun; Ha, Sujin; Lee, Ji Eun; Kim, Hee Cheol
Abstract : DOI: 10.1002/pmic.201900367 A comparative analysis of symmetric arginine methylation between colorectal cancer and adjacent noncancerous tissues from patients is pursued using immunoaffinity enrichment of symmetric dimethylarginine (SDMA)‐containing peptides followed by label‐free LC‐MS/MS. The majority of SDMA residues are flanked by two glycines and many SDMA‐containing proteins are involved in RNA metabolism. The symmetric dimethylation of 74 arginine sites are found to be significantly changed between two sample types. This will provide a new insight to further functional and clinical investigation during colorectal tumorigenesis. More details can be found in article number 1900367 by Yongchul Lim et al.